A Statistical Model to Determine Biomechanical Limits for Physically Safe Interactions With Collaborative Robots - Behrens , R.; Pliske , G.; Umbreit , M.; Piatek , S.; Walcher , F.; Elkmann , N. (Frontiers in Robotics and AI, 2022)
Collaborative robots (cobots) provide a wide range of opportunities to improve the ergonomics and efficiency of manual work stations. ISO/TS 15066 defines power and force limiting (PFL) as one of four safeguarding modes for these robots. PFL specifies biomechanical limits for hazardous impacts and pinching contacts that a cobot must not exceed to protect humans from serious injuries. Most of the limits in ISO/TS 15066 are preliminary, since they are based on unverified data from a literature survey. This article presents a human-subject study that provides new and experimentally verified limits for biomechanically safe interactions between humans and cobots. The new limits are specifically tailored to impact and pinching transferred through blunt and semi-sharp surfaces as they can occur in the event of human error or technical failures. Altogether 112 subjects participated in the study and were subjected to tests with emulated impact and pinching loads at 28 different body locations. During the experiments, the contact force was gradually increased until the load evoked a slightly painful feeling on the subject’s body location under test. The results confirm that the pain thresholds of males and females are different in specific body regions. Therefore, when defining biomechanical limits, the gender difference must be taken into account. A regression model was utilized to incorporate the gender effect as a covariate into a conventional statistical distribution model that can be used to calculate individual limits, precisely fitted to a specific percentile of a mixed group of male and female workers which interacting with cobots.